2021
DOI: 10.1021/acsnano.1c00394
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Particle Tracking Detects Changes in Brain Extracellular Matrix and Predicts Neurodevelopmental Age

Abstract: Brain extracellular matrix (ECM) structure mediates many aspects of neural development and function. Probing structural changes in brain ECM could thus provide insights into mechanisms of neurodevelopment, the loss of neural function in response to injury, and the detrimental effects of pathological aging and neurological disease. We demonstrate the ability to probe changes in brain ECM microstructure using multiple particle tracking (MPT). We performed MPT of colloidally stable polystyrene nanoparticles in or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Glial migration and proliferation in response to hypoxic-ischemic events [ 91 , 92 ], which we also show in our data in response to OGD, has been associated with both the down-regulation of ECM protein expression [ 93 , 94 ] and increased expression of ECM degrading matrix metalloproteinases [ 95 , 96 ]. Changes in brain ECM structure and composition are known to impact the extracellular diffusion of both small molecules [ 83 , 97 ] and nano-sized probes [ 19 , 98 ]. Future work focused on quantifying ECM protein expression through 14DIV and following OGD would provide clarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glial migration and proliferation in response to hypoxic-ischemic events [ 91 , 92 ], which we also show in our data in response to OGD, has been associated with both the down-regulation of ECM protein expression [ 93 , 94 ] and increased expression of ECM degrading matrix metalloproteinases [ 95 , 96 ]. Changes in brain ECM structure and composition are known to impact the extracellular diffusion of both small molecules [ 83 , 97 ] and nano-sized probes [ 19 , 98 ]. Future work focused on quantifying ECM protein expression through 14DIV and following OGD would provide clarity.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that multiple particle tracking (MPT) is capable of detecting dynamic changes in brain ECM microstructure and quantifying both ECS transport properties and geometry with submicron resolution [ 19 ]. Therefore, MPT can be a viable option to study regional differences in the brain extracellular microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Another way is to sequentially combine each constructed model, such that a new model is trained with the knowledge of the entire error that the whole ensemble has learnt so farsuch as gradient boosting techniques (Figure E-ii) . For example, an extreme gradient boosted tree (XGBoost) algorithm trained on fluorescent microscopy tracking of hundreds to thousands of poly­(ethylene glycol)-coated polystyrene nanoparticles effectively predicted the neurodevelopmental age of rats with 86.64% accuracy by studying changes in the brain extracellular matrix . Overall, tree-based ensemble algorithms have immense potential in dealing with complicated feature relationships arising from concurrent monitoring of multiple biomarkers, due to their inherent ability to form robust and generalizable models.…”
Section: For Rapid On-site Prediction Of Diseasesmentioning
confidence: 99%
“…Respectively, to the exploration of the brain’s ECS, SPT methods gave reconstruction of the ECS’s topology and characteristic distances between cell providing transport channels [ 43 , 44 , 45 , 46 , 47 ]. Another usage is the SPT-based data is related to the fact of mutual interchangeability of studying mean-squared displacement (MSD) of random walker exploring either one long track or the evolution of the concentration distribution of a large ensemble of markers in the case of classic diffusion process (ergodicity).…”
Section: Ecs Transport Assessmentmentioning
confidence: 99%
“…The MSD in this case directly gives the value of the diffusion coefficient. Thus, analysing tracks of single particles in different locations of the brain’s ECS, it is possible to get a map of the distribution of local diffusion coefficients, which as revealed widely varies across the ECS [ 45 , 47 , 48 , 49 ].…”
Section: Ecs Transport Assessmentmentioning
confidence: 99%